Enterprise, activism and charity: Mary Pickford and the urban elite of Derby, 1780-1812. (2nd January 2020) - Collinge, Peter
ABSTRACT: Assessing the role of the enterprising middle-ranking widow amongst the urban elite in Derby, England, this article focuses on Mary Pickford, the contribution she made to the early textile industry, her political engagement, and her charitable concerns. The interrelated aspects of Pickford's life simultaneously contributed to her social standing and to Derby's economic development. The East Midlands was synonymous with the large-scale textile concerns of the Strutts and the Arkwrights about whom much has been written. Pickford's moderately-sized business, however, is more representative of the majority about which far less is known. As such, an analysis of her activities, drawn from fragmentary sources, recognises the significance of the individual and the enmeshed nature of female involvement in urban life, thereby adding to a greater understanding of industrial and urban growth in the region.